Development and evaluation of luteolin loaded pegylated bilosome: optimization, in vitro characterization, and cytotoxicity study - Ameeduzzafar Zafar; Nabil K. Alruwaili; Syed Sarim Imam; Omar Awad Alsaidan; Mohd Yasir; Mohammed M. Ghoneim; Sultan Alshehri; Md. Khalid Anwer; Alanood S. Almurshedi; Abdullah S. Alanazi (Taylor & Francis Group, 2021)
The present research was aimed to develop luteolin (LL) loaded pegylated bilosomes (PG-BLs) for oral delivery. The luteolin bilosomes (BLs) were prepared by the thin-film hydration method and further optimized by the Box-Behnken design (four-factors at three-levels). The prepared LL-BLs were evaluated for vesicle size (VS), PDI, zeta potential (ZP), and entrapment efficiency to select the optimized formulation. The optimized formulation was further assessed for surface morphology, drug release, gut permeation, antioxidant, and antimicrobial study. The cytotoxicity study was conducted on breast cancer cell lines (MDA-MB-231 and MCF7). The optimized formulation LL-PG-BLs-opt exhibited a VS of 252.24 ± 3.54 nm, PDI of 0.24, ZP of −32 mV with an encapsulation efficiency of 75.05 ± 0.65%. TEM study revealed spherical shape vesicles without aggregation. The DSC and XRD results revealed that LL was encapsulated into a PG-BLs matrix. LL-PG-BLs-opt exhibited a biphasic release pattern as well as significantly high permeation (p<.05) was achieved vis-a-vis LL-BL-opt and LL dispersion. The antioxidant activity result revealed 70.31 ± 3.22%, 83.76 ± 2.56%, and 96.87 ± 2.11% from LL-dispersion, LL-BLs-opt, and LL-PG-BLs-opt, respectively. Furthermore, LL-PG-BLs-opt exhibited high cell viability on both cell lines than LL-BL-opt and pure LL. The IC50 value was found to be 390 µM and 510 µM against MCF7 and MDA-MB-231 cancer cells, respectively. The antimicrobial activity result exhibited LL-PG-BLs-opt had better antibacterial activity than pure LL against Staphylococcus aureus and Escherichia coli. Hence, PG-BLs might provide an efficient nano oral delivery for the management of the different diseases.